Youtube as alternative media for digital activism in documentary film creative industry - Rospitasari, Marina (Jurnal Studi Komunikasi, 2021)
The development of the digital world provides ample scope to activists who are also engaged in Documentary Film Industry. In line with the democratic and deliberative spirit, YouTube, one of the social media platforms, has become an alternative media with a strategic positioning to be used by film activists to distribute their works. This research applied literature review and descriptive quantitative content analysis as a methodology. Based on alternative media theory, YouTube is alternative media that filmmakers utilise in the documentary film creative industry. Documentary films are products of the film industry and aspiration, identity struggle, and artistic expression. As a media representation of communication technology, YouTube provides ample opportunities for art activists to convey their critical ideas to voicing marginal groups’ aspirations. Based on reviewing the Watchdoc YouTube account, this research findings that YouTube supports filmmakers to develop interactive documentary and collaborative actions with other strategic stakeholders, such as Production House, NGO, individual activists, social communities, and educational institutions. According to the practising of digital activism, this phenomenon gives another perspective about building an activist network. Activism through the creative documentary industry is not reflected as people mobilisations but building engagement through the product (documentary film).